APPLICATION OF AUTHENTIC ASSESSMENT IN LEARNING POETRY TEXTS IN JUNIOR HIGH SCHOOL STUDENTS - Aprilla, Niken; Handayani , Dina Fitria (PT. Antis International Publisher, 2024)
This research aims to investigate the application of authentic assessment in teaching poetry texts at the intermediate (SMP) level and the challenges faced by Indonesian language teachers with errors. In this process. Education is an effort to change a person's attitudes and behavior towards maturity through training and guidance. The 2013 curriculum requires students to be more active and inclusive in the learning process through continuous assessment which includes cognitive, attitude and ability aspects. However, practice in this area places greater emphasis on cognitive aspects, and a full-scale assessment is required to assess a student's overall abilities. This research uses a qualitative approach with descriptive methods. Data was collected through interviews, observation and recording with Indonesian language teachers. Triangulation techniques are used to test the validity of the data. Data analysis was carried out descriptively to obtain an in-depth understanding of the implementation of authentic assessment and the obstacles teachers face in teaching poetry texts.